2013
DOI: 10.1016/j.neulet.2012.10.019
|View full text |Cite
|
Sign up to set email alerts
|

Effects of early rolipram treatment on histopathological outcome after controlled cortical impact injury in mice

Abstract: Traumatic brain injury (TBI) pathology includes contusions, cavitation, cell death; all of which can be exacerbated by inflammation. We hypothesized that an anti-inflammatory drug, rolipram, may reduce pathology after TBI, since in several CNS injury models rolipram reduces inflammation and improves cell survival and functional recovery. Adult male C57BL/6 mice received a craniotomy over the right parietotemporal cortex. Vertically-directed controlled cortical impact (CCI) injury was delivered. Naïve controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 44 publications
0
30
1
Order By: Relevance
“…Thus, it is possible that treatments that selectively increase cAMP levels may not be useful in all brain injury models, since they could effectively decrease cGMP levels as an unintended consequence. This may explain some of the reported discrepancies in the use of PDE4 inhibitors in brain injury [114, 115]. …”
Section: Role Of Cgmp-pdes and Tbimentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is possible that treatments that selectively increase cAMP levels may not be useful in all brain injury models, since they could effectively decrease cGMP levels as an unintended consequence. This may explain some of the reported discrepancies in the use of PDE4 inhibitors in brain injury [114, 115]. …”
Section: Role Of Cgmp-pdes and Tbimentioning
confidence: 99%
“…This was not model-dependent, since this result was observed in two distinct brain injury models, fluid-percussion brain injury and controlled cortical impact [114, 115]. …”
Section: Pde4 Inhibitors As Anti-inflammtory Agents For Tbimentioning
confidence: 99%
“…However, lack of subtype-selective PDE4 inhibitors has hampered the development of this therapeutic approach for TBI [21, 22]. In this study, we characterized the effect of a PDE4B-selective inhibitor, A33, on inflammation, pathology and behavioral deficits after TBI.…”
Section: Introductionmentioning
confidence: 99%
“…This finding agrees with other reports that have shown that rolipram treatment exacerbated neuronal injury in experimental stroke (27-29). In addition to cerebral ischemia, reports have shown exacerbation of brain injury by rolipram treatment in other models of CNS disease (30, 31). One possible mechanism for exacerbation of brain injury by cAMP-stimulating agents such as rolipram is induction of compensatory upregulation of certain PDE4 isoforms (32-34) to accelerate cAMP degradation (35, 36).…”
Section: Discussionmentioning
confidence: 99%